Discrepancies in self-reported and measured anthropometric measurements and indices among older Australians: prevalence and correlates - Jane M. Fry; Jeromey B. Temple (BMC, 2022)
Abstract Background Anthropometric measurements and indices such as weight, height and Body Mass Index (BMI) are often used to assess overall health and nutritional status. Clinicians and epidemiologists often rely on self-reported weight and height to measure BMI. Differences between self-reported and measured weight and height can lead to differences between self-reported and measured BMI, biasing relative risks of diseases associated with differential BMI. Methods Applying regression analysis to a large nationally representative survey data with contemporaneous self-reports and measurements on 3412 individuals aged 65 or over, we provided estimates of the difference between self-reports and measurements of weight, height and BMI for older Australians, analysing demographic, socioeconomic and health correlates of estimated differences. Results We found both males and females underestimated weight, overestimated height and underestimated BMI and there was some evidence these differences increased with age. There was also evidence that these differences were associated with high levels of education and household composition. Conclusion Although average differences were small, for many individuals the differences may be significant, indicating measurements should be taken in clinically focused research and practice. This is important as systematic underestimation of BMI in older adults can have implications for estimating the size of populations at risk of many health conditions, including diabetes, hypertension and functional limitations.